Unveiling Implicit Communication: A Study of Conventional and Conversational Implicatures in Kim Jiyoung, Born 1982 - Angelina, Maria; Darmawan, Ruly Indra ((JELE) Journal Of English Language and Education, 2024)
This study examines Cho Nam-joo's Kim Jiyoung, Born 1982 through the lens of implicature, focusing on how implied meanings function within the narrative. Drawing upon Grice's theory, the analysis identifies instances within the novel where underlying meanings contribute to the reader's understanding of characters, relationships, and social dynamics. The research explores various types of implicatures, including conventional and conversational, to reveal how they shape the reader's interpretation of events and motivations. Examples include instances of indirect communication within the family and broader societal contexts. The analysis extends to the workplace, revealing how implicatures in the novel expose unspoken assumptions and biases. By decoding these implicatures, the research aims to uncover the subtle yet pervasive ways language enriches the narrative. The findings contribute to a deeper understanding of how literary texts can use implicature to create nuanced meanings and engage readers on multiple levels.